Stromal cells engineered to express T cell factors induce robust CLL cell proliferation in vitro and in PDX co-transplantations allowing the identification of RAF inhibitors as anti-proliferative drugs - Hoferkova, Eva; Seda, Vaclav; Kadakova, Sona; Verner, Jan; Loja, Tomas; Matulová, Květoslava; Skuhrova Francova, Hana; Ondrouskova, Eva; Filip, Daniel; Blavet, Nicolas; Boudny, Miroslav; Mladonicka Pavlasova, Gabriela; et al. (Leukemia, 2024)
Several in vitro models have been developed to mimic chronic lymphocytic leukemia (CLL) proliferation in immune niches; however, they typically do not induce robust proliferation. We prepared a novel model based on mimicking T-cell signals in vitro and in patient-derived xenografts (PDXs). Six supportive cell lines were prepared by engineering HS5 stromal cells with stable expression of human CD40L, IL4, IL21, and their combinations. Co-culture with HS5 expressing CD40L and IL4 in combination led to mild CLL cell proliferation (median 7% at day 7), while the HS5 expressing CD40L, IL4, and IL21 led to unprecedented proliferation rate (median 44%). The co-cultures mimicked the gene expression fingerprint of lymph node CLL cells (MYC, NFκB, and E2F signatures) and revealed novel vulnerabilities in CLL-T-cell-induced proliferation. Drug testing in co-cultures revealed for the first time that pan-RAF inhibitors fully block CLL proliferation. The co-culture model can be downscaled to five microliter volume for large drug screening purposes or upscaled to CLL PDXs by HS5-CD40L-IL4 ± IL21 co-transplantation. Co-transplanting NSG mice with purified CLL cells and HS5-CD40L-IL4 or HS5-CD40L-IL4-IL21 cells on collagen-based scaffold led to 47% or 82% engraftment efficacy, respectively, with ~20% of PDXs being clonally related to CLL, potentially overcoming the need to co-transplant autologous T-cells in PDXs.
Keywords: kokultivační techniky; Animals; proliferace buněk; buňky stromatu; inhibitory proteinkinas; Leukemia, Lymphocytic, Chronic, B-Cell; lidé; interleukiny; Mice; T-lymfocyty; myši; xenogenní modely - testy protinádorové aktivity; Protein Kinase Inhibitors; ligand CD40; Coculture Techniques; Stromal Cells; Cell Proliferation; Xenograft Model Antitumor Assays; Interleukins; T-Lymphocytes; zvířata; chronická lymfatická leukemie; CD40 Ligand; Humans